Influence of zinc on severity of common cold in children - Cahalafa Shinta Caesar; Mohammad Juffrie; Sumadiono Sumadiono (Indonesian Pediatric Society, 2012)
Background Symptomatic treatment of common cold in childrendoes not reduce the duration and severity of disease. Since zinc hasbeen used to enhance cellular and humoral immunity, it has thepotential to reduce the severity of the common cold. However, theeffects of zinc on the common cold have been inconclusive. Theuse of zinc to treat cold symptoms deserves further studies.Objective To determine the effect of zinc supplementation onthe severity of the common cold in children.Methods We performed a randomized, doubleô€blind, controlledtrial in children aged 3ô€ 5 years who were diagnosed Mth a commoncold at primary health care centers in Gedongtengen, Umbulharj 0I and Kotagede II, Yogyakarta. Subjects were collected byconsecutive sampling and their parents were interviewed. Severityof illness was categorized as mild, moderate or severe.Results One hundred fourteen patients with common cold weredivided into 2 groups of 57 subjects each. One group receivedzinc supplementation while the other group received a placebo.Subjects with fever received additional paracetamol. After 7 daysof treatment, there were no significant differences in clinicalimprovement in the zinc group (80.7%) compared to that of theplacebo group (78.9%), Pô€‚O.83.Conclusion The severity of the common cold in children aged3ô€5 years was not significantly different in those who receivedzinc supplementation compared to placebo. [Paediatr Indones.2012;52:324-8].